Neonatal Hemoperitoneum Secondary to Hemorrhage from Omental Venous Malformation - So-Hyun Nam (Pediatrics and Neonatology, 2015)
Hemoperitoneum in the neonate is uncommon. We report our experience with a neonate who suddenly developed hemoperitoneum in late gestation. Ascites with right pleural effusion initially suggested fetal hydrops. However, a decrease in hemoglobin with bloody ascites from the paracentesis gave the impression of hemoperitoneum. Ultrasonography and computed tomography showed no abnormality in the solid organs. Using 3-mm laparoscopic exploration, we found the omental mass and excised it. It was histologically confirmed as a venous malformation. Venous malformation of the omentum with significant bleeding requiring exploration is a very rare condition in the neonate, but it should be considered as a cause of neonatal hemoperitoneum.